2004
DOI: 10.1016/j.molcel.2004.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Postreplicative Recruitment of Cohesin to Double-Strand Breaks Is Required for DNA Repair

Abstract: Chromosome stability depends on accurate chromosome segregation and efficient DNA double-strand break (DSB) repair. Sister chromatid cohesion, established during S phase by the protein complex cohesin, is central to both processes. In the absence of cohesion, chromosomes missegregate and G2-phase DSB repair fails. Here, we demonstrate that G2-phase repair also requires the presence of cohesin at the damage site. Cohesin components are shown to be recruited to extended chromosome regions surrounding DNA breaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
442
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(463 citation statements)
references
References 53 publications
16
442
4
1
Order By: Relevance
“…In meiosis, the primary objective is to establish crossover between homologs, although many meiotic DSBs do not lead to crossover formation and may ultimately be repaired by sister chromatid template HR (see section Genome Maintenance and Human Disease) (Hunter 2007). Sister chromatid cohesion ensures the spatial proximity of the template and additional cohesion complexes are loaded after DSB formation, likely to further favor and stabilize sister interactions (Ström et al 2004Ü nal et al 2004Ström and Sjogren 2005;Cortes-Ledesma and Aguilera 2006). Replication-associated cohesion involves acetylation of the Smc3 subunit of cohesion by Eco1, which is induced in S phase and suppressed outside S phase (Ü nal et al 2008).…”
Section: Role Of Cohesion On Template Choicementioning
confidence: 99%
“…In meiosis, the primary objective is to establish crossover between homologs, although many meiotic DSBs do not lead to crossover formation and may ultimately be repaired by sister chromatid template HR (see section Genome Maintenance and Human Disease) (Hunter 2007). Sister chromatid cohesion ensures the spatial proximity of the template and additional cohesion complexes are loaded after DSB formation, likely to further favor and stabilize sister interactions (Ström et al 2004Ü nal et al 2004Ström and Sjogren 2005;Cortes-Ledesma and Aguilera 2006). Replication-associated cohesion involves acetylation of the Smc3 subunit of cohesion by Eco1, which is induced in S phase and suppressed outside S phase (Ü nal et al 2008).…”
Section: Role Of Cohesion On Template Choicementioning
confidence: 99%
“…The eukaryotic chromosome is packaged into chromatin, which adds additional complexity to the control of all chromosomal processes, including recombination [45][46][47][48]. Unlike E. coli, eukaryotic chromosomes possess numerous potential origins of replication, of which only a fraction are used to initiate DNA synthesis in each cell cycle.…”
Section: Recombination-dependent Replication Restart In Eukaryotes: Amentioning
confidence: 99%
“…Phosphorylation of H2AX ("γ-H2AX") is a rapid, evolutionarily conserved event in the DSB response of eukaryotes and marks chromatin for hundreds of kilobases flanking the DSB [129]. H2AX contributes to DSBR, including SCR, by mechanisms that may involve cohesin complexes [46][47][48]130,131]. This "double life" of BRCA1 on ssDNA and on chromatin further underscores the diversity of functions of this protein, which include HR control, transcriptional regulation/gene silencing and DNA damage checkpoint control.…”
Section: Molecular Functions Of Brca1 and Brca2mentioning
confidence: 99%
“…Previous work has shown that Mcd1 is a checkpoint target, and the checkpoint-dependent phosphorylation of Mcd1 was shown to be important for cohesion during G 2 /M. 67 Like MCD1, SWE1 is another switch gene that also plays an important role during G 2 /M transition. SWE1 encodes a protein kinase involved in the inhibition of the cyclin-dependent kinase (CDK) Cdc28.…”
Section: "Switch Genes:" a New Class Of G 1 /S Cell Cycle Genesmentioning
confidence: 99%